HIPE form, manufacturing method thereof and vacuum heat insulating material
The HIPE form addresses the limitations of inorganic fibers and foam-based materials by offering lightweight, efficient vacuum insulation with enhanced thermal performance and reduced manufacturing time through controlled density and compression stress ratios.
Patent Information
- Application Number
- JP2023118285
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-30
AI Technical Summary
Existing vacuum insulation materials using inorganic fibers as core materials face challenges with high mass and low productivity, while foam-based materials offer limited insulation improvement and prolonged space reduction times.
The use of a HIPE form with a specific density range (65-140 kg/m³) and compression stress ratio (σ₅/σ₅₀ ≤ 0.50) as a core material, composed of a styrene monomer-based polymer, allows for efficient gas evacuation and maintains structural integrity, enhancing insulation performance.
The HIPE form provides lightweight vacuum insulation materials with improved thermal insulation and reduced manufacturing time by ensuring the core material maintains its shape and structure, achieving lower thermal conductivity.
Smart Images

Figure 2025015123000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a HIPE foam, a method for producing the same, and a vacuum insulation material. [Background technology]
[0002] In recent years, efforts to reduce greenhouse gas emissions have been promoted to prevent global warming. From this perspective, the use of vacuum insulation materials has been promoted to reduce energy consumption in electrical appliances, vehicles, equipment, buildings, etc. Vacuum insulation materials have an outer packaging material and a core material enclosed within the outer packaging material. The internal space of the vacuum insulation material is decompressed, and high insulation properties are achieved by suppressing heat transfer due to convection, etc.
[0003] Conventionally, inorganic fibers with low thermal conductivity, such as glass wool, have been used as the core material for vacuum insulation materials. However, when inorganic fibers are used as the core material, it is necessary to encapsulate a relatively large amount of inorganic fibers in the outer packaging material, taking into consideration the shrinkage that occurs when the internal space is decompressed. Therefore, there is a problem that vacuum insulation materials having a core material made of inorganic fibers tend to be large in mass.
[0004] In order to solve this problem, the use of a resin foam, which is lighter than inorganic fibers, as the core material of the vacuum insulation material has been considered. For example, Patent Document 1 describes the use of an open-cell microcellular alkenyl aromatic polymer foam as the core material of the vacuum insulation material. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 11-504362 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in Patent Document 1, there is room for improvement in order to further improve the heat insulating properties of the vacuum insulation material when the foam is used as the core material of the vacuum insulation material. Also, when the foam of Patent Document 1 is used as the core material of the vacuum insulation material, it takes a relatively long time to reduce the pressure in the internal space of the vacuum insulation material, which causes a problem of low productivity.
[0007] The present invention has been made in consideration of the above background, and aims to provide a HIPE foam that can easily produce a vacuum insulation material that is easy to manufacture, lightweight, and has good thermal insulation properties, a manufacturing method thereof, and a vacuum insulation material comprising this HIPE foam. [Means for solving the problem]
[0008] One aspect of the present invention is a HIPE foam according to the following items (1) to (3).
[0009] [1] A plate-shaped HIPE foam used as a core material in a vacuum insulation material having an outer packaging material and a core material enclosed in the outer packaging material, The apparent density of the HIPE foam is 65 kg / m 3 More than 140kg / m 3 is as follows: Compressive stress σ of the HIPE foam at 50% strain 50 Ratio of compressive stress σ5 at 5% strain to σ5 / σ 50 is between 0.17 and 0.50, HIPE form.
[0010] [2] The HIPE foam described in [1], wherein the compressive stress σ5 at 5% strain of the HIPE foam is 105 kPa or more. [3] The HIPE foam according to [1] or [2], wherein the HIPE foam is composed of a crosslinked polymer of a styrene-based monomer.
[0011] Another aspect of the present invention is a vacuum insulation material according to the following [4].
[0012] [4] A packaging material and a core material enclosed in the packaging material, A vacuum insulation material, wherein the core material is composed of the HIPE foam according to any one of [1] to [3].
[0013] Still another aspect of the present invention resides in the method for producing a HIPE foam according to the following items [5] to [7].
[0014] [5] Apparent density is 35kg / m 3 More than 70kg / m 3 Prepare the following sheet-shaped HIPE foam (X), The HIPE foam (X) is compressed to a compression ratio C of 0.2 to 0.7 inclusive, the compression ratio C being expressed by the following formula (1) in a state where the temperature of the HIPE foam (X) is equal to or higher than the glass transition temperature of the HIPE foam (X); The HIPE foam (X) in a compressed state is cooled to a temperature below the glass transition temperature, whereby the compressive stress at 50% strain σ 50 Ratio of compressive stress σ5 at 5% strain to σ5 / σ 50 A method for producing a HIPE foam, comprising forming a HIPE foam having a viscosity of 0.17 or more and 0.50 or less. C = (t0-t1) / t0 (1) (In the above formula (1), t0 is the thickness (unit: mm) of the HIPE foam (X) before compression, and t1 is the thickness (unit: mm) of the HIPE foam (X) in the compressed state.)
[0015] [6] The method for producing a HIPE foam according to [5], wherein the average strut width of the HIPE foam (X) before compression is 2 μm or more and 10 μm or less. [7] The method for producing a HIPE foam according to [5] or [6], wherein the compressive stress σx5 at 5% strain of the HIPE foam (X) before compression is 140 kPa or more. Effect of the Invention
[0016] According to the above-mentioned aspect, it is possible to provide a HIPE foam that can easily produce a vacuum insulation material that is easy to manufacture, lightweight, and has good thermal insulation properties, a manufacturing method thereof, and a vacuum insulation material including this HIPE foam. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is an explanatory diagram showing an enlarged photograph of a cross section of a HIPE foam (X). [Diagram 2] FIG. 2 is an explanatory diagram showing an enlarged photograph of a cross section of a HIPE foam that has been compressed at a temperature above its glass transition temperature and has retained its compressed shape. [Diagram 3] FIG. 3 is an explanatory diagram showing an example of a temperature-storage modulus curve showing the relationship between the temperature T and the storage modulus E′ of the HIPE foam (X). [Figure 4] FIG. 4 is a partial cross-sectional view showing a main part of the vacuum insulation material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] (HIPE Form) HIPE foam is a porous polymer also called polyHIPE foam, polyHIPE material, HIPE-derived foam material, high internal phase emulsion porous body, high internal phase emulsion foam body, etc. HIPE foam can be obtained, for example, by polymerizing monomers in a water-in-oil type high internal phase emulsion (i.e., HIPE) in which a high ratio of aqueous phase is contained in an organic phase to obtain a polymerization product (a cross-linked polymer containing water), and then drying the polymerization product. The HIPE foam obtained in this manner has an open-cell structure in which many bubbles exist in the structure and many through-holes are formed in the bubble walls present between adjacent bubbles. Since the HIPE foam has an open-cell structure, the gas inside the HIPE foam is easily exhausted to the outside. Therefore, when the HIPE foam is used as the core material of a vacuum insulation material, the time required for the decompression process can be shortened.
[0019] The HIPE foam can be obtained, for example, by polymerizing a styrene-based monomer in a water-in-oil type high internal phase emulsion in which a high ratio of the aqueous phase is encapsulated in an organic phase to obtain a polymerization product, and then drying the polymerization product. The HIPE foam thus obtained is composed of a crosslinked polymer containing a monomer component derived from a styrene-based monomer. More specifically, the HIPE foam contains a monomer component derived from a styrene-based monomer in the polymer skeleton of the crosslinked polymer. The HIPE foam can also be obtained, for example, by polymerizing a styrene-based monomer in the presence of a crosslinking agent in a water-in-oil type high internal phase emulsion in which a high ratio of the aqueous phase is encapsulated in an organic phase to obtain a polymerization product, and then drying the polymerization product. The HIPE foam thus obtained is composed of a crosslinked polymer containing a monomer component derived from a styrene-based monomer and a component derived from a crosslinking agent. More specifically, the HIPE foam contains a monomer component derived from a styrene-based monomer and a component derived from a crosslinking agent in the polymer skeleton of the crosslinked polymer.
[0020] HIPE foam is a porous cured material obtained by curing a high internal phase emulsion, and the cell walls can be said to be composed of a crosslinked polymer (e.g., a styrene-based polymer). The cells can also be said to be pores. The shape of the cell walls and cells in HIPE foam reflects the dispersion form of the organic phase and the aqueous phase in the high internal phase emulsion and the dispersion form of the aqueous phase (i.e., the dispersed phase) during polymerization.
[0021] In the manufacturing process of HIPE foam, the crosslinked polymer is difficult to stretch. HIPE foam can be easily distinguished from foams produced by stretching during production, such as foams obtained by extrusion foaming using an extruder, and foamed bead moldings obtained by foaming expandable resin beads and molding the expanded beads in a mold.
[0022] In addition, since HIPE foam does not require the use of volatile components such as foaming agents in its manufacturing process, the amount of gas emitted from the HIPE foam can be easily reduced even when no operation is performed to remove volatile components from the crosslinked polymer. Furthermore, since the HIPE foam has the open cell structure described above, the gas present in the cells of the HIPE foam can easily move to the outside of the HIPE foam. Therefore, by using the HIPE foam as the core material of the vacuum insulation material, the gas present in the internal space can be quickly exhausted during the manufacturing process of the vacuum insulation material. As a result, the manufacturability of the vacuum insulation material can be easily improved.
[0023] [Apparent density of HIPE foam] The apparent density of the HIPE foam is 65 kg / m 3 More than 140kg / m 3 The apparent density of the HIPE foam is set within the above-mentioned specific range, so that the strength of the HIPE foam can be set within a range suitable for use as a core material of a vacuum insulation material. Therefore, by using such a HIPE foam as a core material of a vacuum insulation material, the shape of the core material can be maintained even when it is enclosed in an outer packaging material. Furthermore, by using a HIPE foam having an apparent density within the above-mentioned specific range as a core material of a vacuum insulation material, the thermal insulation properties of the vacuum insulation material can be improved.
[0024] If the apparent density of the HIPE foam is too low, the strength of the HIPE foam will be insufficient, and when the internal space is decompressed during the manufacturing process of the vacuum insulation material, the core material will easily shrink due to the pressure difference between the atmospheric pressure and the pressure of the internal space. Therefore, in this case, the dimensions of the vacuum insulation material may easily deviate from the desired dimensions. In some cases, the air bubbles may be crushed, making it impossible to form a vacuum space inside the vacuum insulation material. On the other hand, if the apparent density of the HIPE foam is too high, the insulating properties of the vacuum insulation material may be reduced.
[0025] The apparent density of HIPE foam is 70kg / m 3It is preferable that the resistance is 75 kg / m or more. 3 More preferably, it is 80 kg / m or more. 3 In this case, the thermal conductivity of the HIPE foam itself can be further reduced, and the thermal insulation property of the vacuum insulation material can be further improved.
[0026] The apparent density of HIPE foam is 135kg / m 3 It is preferable that the thickness is less than 130 kg / m 3 More preferably, it is 125 kg / m or less. 3 More preferably, it is 120 kg / m or less. 3 It is particularly preferable that the HIPE foam is no greater than 100%. In this case, the weight of the HIPE foam can be reduced more easily.
[0027] In determining the preferred range of the apparent density of the HIPE foam, the upper and lower limits of the preferred range of the apparent density of the HIPE foam described above can be combined arbitrarily. For example, the preferred range of the apparent density of the HIPE foam is 65 kg / m 3 More than 135kg / m 3 It may be less than 70 kg / m 3 More than 135kg / m 3 may be less than 75 kg / m 3 More than 130kg / m 3 It may be less than 80 kg / m 3 More than 125kg / m 3 It may be less than 80 kg / m 3 More than 120kg / m 3 It may be the following.
[0028] The apparent density of the HIPE foam described above is calculated by dividing the mass of the HIPE foam by the volume of the HIPE foam. The volume of the HIPE foam can be calculated based on the outer dimensions of the HIPE foam.
[0029] The apparent density of the HIPE foam is adjusted to be within the above range by adjusting the ratio of the amount of the organic phase (specifically, the total amount of the styrene-based monomer, crosslinking agent, emulsifier, and polymerization initiator) to the amount of the aqueous phase (specifically, the amount of the aqueous liquid), and the compression amount of the HIPE foam, etc., in the manufacturing method of the HIPE foam described below.
[0030] [HIPE foam compression stress ratio] Compressive stress σ of HIPE foam at 50% strain 50 Ratio of compressive stress σ5 at 5% strain to σ5 / σ 50 The ratio σ5 / σ is 0.17 or more and 0.50 or less. 50 The HIPE foam having a specific range is subjected to the following treatment after the HIPE foam is formed. That is, the HIPE foam is compressed while being heated to a temperature equal to or higher than the glass transition temperature after the HIPE foam is formed, and cooled to a temperature lower than the glass transition temperature while maintaining the compressed state. By subjecting the HIPE foam to such treatment, a HIPE foam that maintains its compressed shape can be obtained. Then, by using the HIPE foam that maintains its compressed shape as the core material of the vacuum insulation material, the thermal insulation property of the vacuum insulation material can be improved.
[0031] The ratio σ5 / σ 50 The range is preferably 0.17 to 0.45, more preferably 0.17 to 0.40, and even more preferably 0.18 to 0.35. In this case, when the HIPE foam is used as a core material of a vacuum insulation material, the thermal conductivity of the vacuum insulation material can be further reduced, and the insulation performance can be further improved.
[0032] In addition, the compressive stress σ5 at 5% strain and the compressive stress σ at 50% strain of HIPE foam are 50 is a value obtained by measuring based on JIS K6767:1999. HIPE foam compressive stress at 5% strain σ5 and compressive stress at 50% strain σ 50The specific measurement method is as follows. First, a test piece 50 mm long, 50 mm wide, and 20 mm thick is cut out from near the center of the HIPE foam, excluding the skin surface, i.e., the surface that was in contact with the container during the polymerization of the HIPE. If the thickness of the HIPE foam before cutting is less than 20 mm, multiple small pieces 50 mm long and 50 mm wide that do not include the skin surface can be prepared, and these small pieces can be stacked together to a total thickness of 20 mm to form a laminate that can be used as the test piece.
[0033] Next, the test specimen is conditioned by placing it in an environment of 23°C and 50% humidity. Then, a compression test is performed using the conditioned test specimen to obtain the compressive stress at 5% strain σ5 and the compressive stress at 50% strain σ of the HIPE foam. 50 The compression test can be performed using a tabletop precision universal testing machine (for example, Shimadzu Corporation's "AGS-10kNX"). The compression speed in the compression test can be set to 10 mm / min. The compression stress at 5% strain σ5 of the HIPE foam obtained by the above method can be converted to the compression stress at 50% strain σ 50 By dividing by the ratio σ5 / σ 50 can be calculated.
[0034] The reasons why the insulating properties of vacuum insulation material can be improved by using HIPE foam, which maintains its shape when compressed, as the core material of the vacuum insulation material are, for example, as follows.
[0035] As described above, the HIPE foam is a porous polymer having an open-cell structure. Figure 1 shows an example of an enlarged photograph of a cross section of the HIPE foam (X) before compression. The HIPE foam (X) has cell walls 11 made of a cross-linked polymer. The HIPE foam (X) has a cell structure in which a large number of cells 12 are uniformly present, and also has an open-cell structure in which a large number of through-holes 13 are formed that penetrate the cell walls 11 and communicate between adjacent cells.
[0036] The cell wall 11 has columnar struts 111 that divide adjacent through holes 13, and a hub 112 where the struts 111 join together. In FIG. 1, the cell 12 is a portion surrounded by the cell wall 11. The through hole 13 is a hole that penetrates the cell wall 11 and communicates between adjacent cells 12. Specifically, the through hole 13 is a hole that is formed in the cell wall 11 and communicates between adjacent cells 12 with the cell wall 11 in between. The through hole 13 can also be called a through window or a connecting hole.
[0037] In the manufacturing process, the HIPE foam is compressed while being heated to a temperature equal to or higher than the glass transition temperature, and then cooled to a temperature below the glass transition temperature while maintaining the compressed shape. The shape of the HIPE foam 1 compressed in this manner is stabilized in a state in which the cells 12 are crushed in the compression direction, as shown in Figure 2. The HIPE foam is subjected to the above-mentioned treatment, and the compressive stress σ of the HIPE foam at 50% strain is 50 and the ratio of compressive stress σ5 at 5% strain σ5 / σ 50 Within the above-mentioned specific range, it is possible to obtain a moderately compressed HIPE foam while maintaining some of the internal structure of the HIPE foam (X) before compression, such as the cell walls, cells, through-holes, and struts. This allows a vacuum insulation material to be obtained that has a lower thermal conductivity when the HIPE foam is used as a core material of the vacuum insulation material.
[0038] [HIPE foam compressive stress at 5% strain] The HIPE foam preferably has a compressive stress σ5 at 5% strain of 105 kPa or more. A HIPE foam having a compressive stress σ5 at 5% strain within the above-mentioned specific range is encapsulated inside an outer packaging material and is unlikely to shrink even when a pressure difference is applied between the inside and outside of the outer packaging material. Therefore, by using such a HIPE foam as the core material of a vacuum insulation material, a vacuum-state internal space can be more reliably formed inside the outer packaging material, and the insulation properties of the vacuum insulation material can be more reliably improved.
[0039] From the viewpoint of increasing the strength of the HIPE foam and further suppressing the shrinkage of the core material, the compressive stress σ5 at 5% strain of the HIPE foam is preferably 120 kPa or more, more preferably 140 kPa or more, and particularly preferably 160 kPa or more.
[0040] [Crosslinked polymer] HIPE foam is composed of a crosslinked polymer of a styrene-based monomer. That is, the resin portion of the HIPE foam is a polymer obtained by polymerizing a styrene-based monomer in the presence of a crosslinking agent, and contains a monomer component derived from the styrene-based monomer and a component derived from the crosslinking agent. The proportion of the styrene-based monomer in 100% by mass of the monomer components constituting the crosslinked polymer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0041] Examples of styrene-based monomers include styrene compounds having one vinyl group on an aromatic ring, such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-methoxystyrene, pn-butylstyrene, pt-butylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, 2,4,6-tribromostyrene, styrenesulfonic acid, and sodium styrenesulfonate.
[0042] As the styrene-based monomer, it is preferable to use styrene. When styrene is used as the styrene-based monomer, the content of styrene in the styrene-based monomer is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more.
[0043] The resin portion of the HIPE foam may contain a monomer component derived from an acrylic monomer within a range that does not impair the above-mentioned action and effect. In other words, the resin portion of the HIPE foam may be a crosslinked copolymer obtained by polymerizing a styrene monomer and an acrylic monomer in the presence of a crosslinking agent. Examples of the acrylic monomer include alkyl acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, isobornyl acrylate, dicyclopentanyl acrylate, and adamantyl acrylate; and alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, benzyl methacrylate, isobornyl methacrylate, dicyclopentanyl methacrylate, and adamantyl methacrylate. Examples of the acrylic monomer include (meth)acrylic esters having one vinyl group per molecule. In addition, among the monomer components constituting the crosslinked polymer, the proportion of the acrylic monomer component is preferably 30 mass% or less, more preferably 20 mass% or less, and even more preferably 10 mass% or less, relative to 100 mass% in total of the styrene monomer component and the acrylic monomer component.
[0044] A crosslinking agent is a compound that crosslinks (bonds) between polymer chains that constitute a polymer to form a crosslinked structure in the polymer. More specifically, as the crosslinking agent, for example, a vinyl-based compound having at least two crosslinkable functional groups selected from a vinyl group and an isopropenyl group in the molecule is used. When the crosslinked polymer contains a crosslinking agent component, the rigidity and toughness of the crosslinked polymer can be increased. The vinyl-based compound also includes a compound containing a vinyl group and / or an isopropenyl group in the structure of the crosslinkable functional group, such as an acryloyl group or a methacryloyl group. From the viewpoint of stably polymerizing the crosslinking agent, the number of crosslinkable functional groups contained in the crosslinking agent is preferably 6 or less, more preferably 5 or less, and more preferably 4 or less per molecule of the crosslinking agent. In addition, from the viewpoint of making it easier to increase the toughness of the crosslinked polymer, the crosslinking agent preferably has crosslinkable functional groups at least at both ends of the molecule, and more preferably has crosslinkable functional groups only at both ends of the molecule.
[0045] Examples of the crosslinking agent include vinyl compounds having two or more crosslinkable functional groups per molecule, such as divinylbenzene, triallyl isocyanurate, esters of polyhydric alcohols and (meth)acrylic acid, esters of polyether glycols and (meth)acrylic acid, esters of urethane oligomers and (meth)acrylic acid, esters of epoxy oligomers and (meth)acrylic acid, and (meth)acrylic-modified silicones. Examples of the esters of polyhydric alcohols and (meth)acrylic acid include butanediol (meth)acrylates such as butanediol diacrylate; hexanediol (meth)acrylates such as hexanediol diacrylate; nonanediol (meth)acrylates such as nonanediol diacrylate; decanediol (meth)acrylates such as decanediol diacrylate; trimethylolpropane (meth)acrylates such as trimethylolpropane triacrylate; and pentaerythritol (meth)acrylates such as pentaerythritol tetraacrylate. Examples of the ester of polyether glycol and (meth)acrylic acid include polyethylene glycol (meth)acrylates such as polyethylene glycol diacrylate; polypropylene (meth)acrylates such as polypropylene glycol diacrylate; and polytetramethylene glycol (meth)acrylates such as polytetramethylene glycol diacrylate. The crosslinkable functional group in the crosslinking agent is preferably a vinyl group and / or an isopropenyl group. These crosslinking agents may be used alone, or two or more crosslinking agents may be used in combination. In other words, the crosslinking agent component contained in the HIPE foam may be one type, or two or more types.
[0046] From the viewpoint of increasing the strength of the HIPE foam and making it easier to maintain the shape of the core material even when it is enclosed in an outer packaging material, the main component of the crosslinking agent is preferably a vinyl-based compound having a molecular weight of 100 to 400, and more preferably a vinyl-based compound having a molecular weight of 100 to 250. The main component of the crosslinking agent means a component that accounts for 50% by mass or more of the crosslinking agent. The proportion of the vinyl-based compound that is the main component of the crosslinking agent is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more.
[0047] When the HIPE foam contains a styrene-based monomer component, i.e., a monomer component derived from a styrene-based monomer, and a crosslinking agent component, i.e., a component derived from a crosslinking agent, the content of the styrene-based monomer component in the HIPE foam is preferably 80 parts by mass or more and 97 parts by mass or less, and more preferably 85 parts by mass or more and 95 parts by mass or less, relative to 100 parts by mass of the total of the styrene-based monomer component and the crosslinking agent component. In this case, the strength of the HIPE foam can be more easily increased to a range suitable for use as a core material for a vacuum insulation material.
[0048] [HIPE foam shape] The HIPE foam has a plate shape from the viewpoint of use as a core material of a vacuum insulation material and manufacturing. The thickness of the HIPE foam is preferably 2 mm or more and 30 mm or less.
[0049] (HIPE foam manufacturing method) As described above, the HIPE foam can be obtained by compressing the HIPE foam (X) while the temperature of the HIPE foam (X) is equal to or higher than the glass transition temperature, and then cooling the HIPE foam (X) to a temperature lower than the glass transition temperature while maintaining the compressed shape. The method for producing the HIPE foam will be described in more detail below.
[0050] [HIPE Form (X)] Before compression, HIPE foam (X) has an apparent density of 35 kg / m 3 More than 70kg / m 3 The following HIPE foams can be used. The method for measuring the apparent density of the HIPE foam (X) is the same as the method for measuring the apparent density of the HIPE foam described above.
[0051] [HIPE foam (X) compressive stress at 5% strain σx5] The compressive stress σx5 at 5% strain of the HIPE foam (X) before compression is preferably 140 kPa or more, more preferably 200 kPa or more, and even more preferably 300 kPa or more. In this case, when the HIPE foam after compression and cooling is used as a core material to manufacture a vacuum insulation material, the shrinkage of the vacuum insulation material can be more easily reduced. The upper limit of the compressive stress σx5 at 5% strain of the HIPE foam (X) is not particularly limited, but the upper limit of the compressive stress σx5 at 5% strain of the HIPE foam (X) made of a crosslinked polymer of a styrene-based monomer is usually about 900 kPa. The method for measuring the compressive stress σx5 at 5% strain of the HIPE foam (X) is the same as the method for measuring the compressive stress σ5 at 5% strain of the HIPE foam described above.
[0052] [Compressive stress ratio of HIPE foam (X)] Compressive stress σx at 50% strain of HIPE foam (X) before compression 50 Ratio of compressive stress at 5% strain σx5 to σx5 / σx 50 is preferably 0.7 or more, more preferably 0.8 or more, and even more preferably 0.85 or more. In this case, the strength of the HIPE foam after compression and cooling can be easily increased to a range suitable for use as a core material of a vacuum insulation material. From the viewpoint of obtaining such an effect, the ratio σx5 / σx 50 The upper limit of the compressive stress σx at 50% strain of the HIPE foam (X) is not particularly limited. 50 Ratio of compressive stress at 5% strain σx5 to σx5 / σx 50The upper limit of is about 1.0. The compressive stress σx of HIPE foam (X) at 50% strain is 50 The measurement method is the compressive stress σ at 50% strain of the HIPE foam mentioned above. 50 The measurement method is the same as that of
[0053] [Average bubble diameter of HIPE foam (X)] The average bubble diameter of the HIPE foam (X) before compression is preferably 10 μm to 100 μm, more preferably 15 μm to 90 μm, and even more preferably 20 μm to 80 μm. By setting the average bubble diameter of the HIPE foam (X) within the above specific range, the effect of improving the thermal insulation of the vacuum insulation material can be more reliably obtained.
[0054] The average bubble diameter of the HIPE foam (X) is specifically the average value of the circle-equivalent diameter of the bubbles. The circle-equivalent diameter of the bubbles is the diameter of a circle having the same area as the area of the bubbles in the cross section of the HIPE foam (X). The average bubble diameter of the HIPE foam (X) can be obtained, for example, by image analysis of the open-cell structure of the HIPE foam (X) before compression. A more detailed method for measuring the average bubble diameter will be described in the Examples.
[0055] [Average strut width of HIPE foam (X)] The average strut width of the HIPE foam (X) before compression is preferably 2 μm or more and 10 μm or less, more preferably 2 μm or more and 8 μm or less, and even more preferably 2 μm or more and 7 μm or less. In this case, the effect of improving the heat insulation of the vacuum insulation material can be obtained more reliably.
[0056] The method for measuring the average strut width in the HIPE foam (X) is as follows. First, the HIPE foam (X) before compression is cut at an arbitrary cross section to expose the cut surface. Next, the cut surface is observed using a scanning electron microscope or the like to obtain an enlarged photograph of the cut surface. On this enlarged photograph, multiple struts are randomly selected, and the width of the narrowest part of each strut is measured. The arithmetic mean value of the strut widths thus obtained is taken as the average strut width. The number of struts used to calculate the average strut width is not particularly limited, but the more struts there are, the more accurate the average strut width can be calculated. From this viewpoint, the number of struts used to calculate the average strut width is preferably, for example, 20 or more.
[0057] The average strut width of the HIPE foam (X) can be controlled by adjusting the droplet size of the aqueous phase (i.e., the dispersed phase) of the high internal phase emulsion and the ratio of the amount of the organic phase to the amount of the aqueous phase in the manufacturing method of the HIPE foam (X) described below. For example, the average strut width of the HIPE foam (X) can be narrowed by reducing the amount of the organic phase. Also, even if the amount of the organic phase is the same, increasing the power during stirring reduces the droplet size, and the average strut width of the HIPE foam (X) can be narrowed.
[0058] [Glass transition temperature of HIPE foam (X)] The glass transition temperature Tg of the HIPE foam (X) is preferably 70° C. or more and 150° C. or less, more preferably 80° C. or more and 140° C. or less, and even more preferably 90° C. or more and 130° C. or less. By using a HIPE foam produced from such a HIPE foam (X) as a core material, a vacuum insulation material that can be used in higher temperature environments can be obtained. In this case, the strength of the HIPE foam after compression can be more easily increased to a range suitable for use as a core material for a vacuum insulation material.
[0059] The glass transition temperature Tg of the HIPE foam (X) is measured based on JIS K7121:1987. Specifically, a test piece made of a crosslinked polymer is prepared, and the condition of the test piece is adjusted based on "(3) Measurement of glass transition temperature after a certain heat treatment" in "3. Conditioning of test piece" in JIS K7121:1987. Then, a differential scanning calorimetry (DSC) is performed on the resin constituting the conditioned test piece to obtain a DSC curve. The midpoint glass transition temperature in the DSC curve obtained in this manner is taken as the glass transition temperature Tg of the HIPE foam (X).
[0060] The glass transition temperature Tg of the HIPE foam (X) is adjusted to fall within the above range by adjusting the type and mixing ratio of the styrene monomer, the type and mixing ratio of the crosslinking agent, etc., used in producing the HIPE foam (X).
[0061] [Molecular weight between crosslink points of HIPE foam (X)] The molecular weight Mc between crosslinks of HIPE foam (X) is 8×10 3 More than 2×10 5 It is preferable that the value is less than 1×10 4 More than 1×10 5 More preferably, it is 2×10 4 8×10 or more 4 In this case, the strength of the HIPE foam after compression and cooling can be more easily increased to a range suitable for use as the core material of a vacuum insulation material.
[0062] The molecular weight Mc between crosslinks of the HIPE foam (X) is measured as follows. The dynamic viscoelasticity measurement is performed on the HIPE foam (X) under the following measurement conditions: frequency: 1 Hz, load: 98 mN, and deformation mode: compression. During the temperature rise process of the dynamic viscoelasticity measurement, the temperature-storage modulus curve (hereinafter referred to as the "T-E' curve") obtained by plotting the temperature on the horizontal axis and the storage modulus E' on the vertical axis shows a relatively flat shape until the temperature of the HIPE foam (X) exceeds the glass transition temperature Tg. When the temperature of the HIPE foam (X) rises to the vicinity of the glass transition temperature Tg, the crosslinked polymer constituting the HIPE foam (X) transitions from a glassy state to a rubbery state. When the crosslinked polymer transitions from a glassy state to a rubbery state, the storage modulus E' in the T-E' curve drops sharply (see FIG. 3).
[0063] After the temperature of the HIPE foam (X) exceeds the glass transition temperature Tg, the T-E' curve again shows a relatively flat shape. The flat portion of the T-E' curve after exceeding the glass transition temperature Tg is called the plateau region (rubber-like flat portion). In the plateau region, E' is proportional to the temperature, so the molecular weight Mc between crosslinking points can be calculated from the following formula (I). Mc = 2(1 + μ)ρRT / E' (I)
[0064] In the above formula (I), μ is the Poisson's ratio, and ρ is the apparent density (unit: kg / m) of the HIPE foam (X). 3 ), R is the gas constant, T is the temperature (unit: K) at any point on the rubbery flat, and E' is the storage modulus (unit: kPa) at that temperature T. The value of Poisson's ratio μ is specifically 0.5, and the value of the gas constant R is specifically 8.314 J / (K mol).
[0065] From the viewpoint of appropriately calculating the molecular weight Mc between crosslinking points, it is preferable that the temperature T used for calculating the molecular weight Mc between crosslinking points is selected from the range of Tg+50°C to Tg+80°C (wherein Tg is the glass transition temperature of the HIPE foam (X)).
[0066] The Poisson's ratio is a value specific to a material, and is calculated by dividing the strain that occurs in the direction perpendicular to the stress when a stress is applied to an object by the strain that occurs in the direction parallel to the stress, and multiplying this value by -1. Theoretically, the Poisson's ratio ranges from -1 to 0.5. When the Poisson's ratio is a negative value, it means that when the HIPE foam (X) is crushed in the vertical direction, it is also crushed in the horizontal direction. Conversely, when the Poisson's ratio is a positive value, it means that when the HIPE foam (X) is crushed in the vertical direction, it stretches in the horizontal direction. Under the measurement conditions of the dynamic viscoelasticity measurement described above, the strain generated in the crosslinked polymer that constitutes the HIPE foam (X) is very small and can be considered to cause no volume change, so the storage modulus E' and the molecular weight between crosslinking points Mc are calculated under the condition of constant volume, i.e., a Poisson's ratio of 0.5.
[0067] The molecular weight Mc between crosslinking points of the HIPE foam (X) can be reduced by adding a crosslinking agent when producing the HIPE foam (X), and can be adjusted to a desired value by adjusting the type and mixing ratio of the crosslinking agent, the type and mixing ratio of the monomer, etc. For example, the molecular weight between crosslinking points can be reduced by adding a large amount of the crosslinking agent component to the HIPE foam (X).
[0068] [HIPE foam (X) manufacturing method] The HIPE foam (X) is obtained by polymerizing a water-in-oil type high internal phase emulsion. The organic phase of the water-in-oil type high internal phase emulsion is a continuous phase containing, for example, a styrene-based monomer, an emulsifier, a polymerization initiator, etc., and the aqueous phase is a dispersed phase containing water such as deionized water. The organic phase of the water-in-oil type high internal phase emulsion may contain a crosslinker as necessary.
[0069] The method for producing the HIPE foam (X) includes, for example, an emulsification step of forming a water-in-oil type high internal phase emulsion in which an aqueous phase containing water is encapsulated in an organic phase containing a styrene-based monomer, an emulsifier, and a polymerization initiator, and a polymerization step of polymerizing a styrene-based monomer in the water-in-oil type high internal phase emulsion filled in a reaction vessel. and a drying step for drying the polymerization product obtained in the polymerization step to obtain a HIPE foam (X).
[0070] ·Emulsification process In the emulsification step, an oily liquid (organic phase) containing organic substances such as a styrene monomer, an emulsifier, and a polymerization initiator and an aqueous liquid (aqueous phase) containing water are mixed and emulsified to prepare a water-in-oil type high internal phase emulsion. In the emulsification step, a high internal phase emulsion can be prepared by mixing an oily liquid and an aqueous liquid so that the aqueous phase is, for example, three times or more of the organic phase in volume ratio. The ratio of the aqueous phase contained in the organic phase can be adjusted by the mass ratio of the organic phase to the aqueous phase. The content of the aqueous phase in the high internal phase emulsion is preferably 250 parts by mass or more and 3000 parts by mass or less, more preferably 400 parts by mass or more and 2500 parts by mass or less, and even more preferably 500 parts by mass or more and 2000 parts by mass or less, relative to 100 parts by mass of the organic phase.
[0071] The method of emulsifying the oily liquid and the aqueous liquid is not particularly limited, but may be a method of emulsifying by starting stirring the oily liquid and the aqueous liquid in a stirring vessel, or a method of adding only the oily liquid in a stirring vessel and starting stirring, and adding the aqueous liquid to the oily liquid in the vessel under stirring using a pump or the like to emulsify. When adding the aqueous liquid to the oily liquid using a pump or the like, the addition rate of the aqueous liquid is not particularly limited, but may be appropriately adjusted within a range of, for example, 10% by mass / min to 1000% by mass / min relative to 100% by mass of the oily liquid. The addition rate of the aqueous liquid is more preferably 100% by mass / min to 800% by mass / min relative to 100% by mass of the oily liquid (organic phase), and even more preferably 200% by mass / min to 600% by mass / min. Furthermore, the specific embodiment of the emulsification step is not particularly limited, and various embodiments can be employed, such as a batch-type emulsification step in which emulsification is performed using a stirring vessel equipped with a stirring device or a centrifugal shaker, and a continuous emulsification step in which an oily liquid and an aqueous liquid are continuously supplied and mixed in a line equipped with a static mixer, a mesh, or the like.
[0072] The stirring speed in the emulsification step is not particularly limited. For example, the stirring power density is 0.01 kW / m 3 More than 10kW / m 3 From the viewpoint of more easily obtaining the HIPE foam (X) having a desired cell structure, the stirring power density in the emulsification step is preferably 0.03 kW / m 3 More than 7kW / m 3 It is more preferable that the stirring power density (unit: kW / m 3 ) is calculated by calculating the power (unit: kW) required for stirring from the torque (unit: N m) and rotation speed (unit: rpm) of the stirring device used in the emulsification process, and multiplying this power by the volume (unit: m 3 ) can be calculated by dividing it by
[0073] The aqueous phase may contain water such as deionized water, a polymerization initiator, an electrolyte, etc. In the emulsification step, for example, an oily liquid and an aqueous liquid are prepared, and the aqueous liquid is added to the oily liquid under stirring to prepare a high internal phase emulsion. In the emulsification step, additives such as a flame retardant, a flame retardant auxiliary, a light resistance agent, and a colorant may be appropriately blended into the aqueous phase and / or the organic phase.
[0074] The flame retardant is used to improve the flame retardancy of the HIPE foam (X). Examples of the flame retardant include organic compounds containing halogen, phosphorus, nitrogen, silicone, etc.; inorganic compounds containing metal hydroxide, phosphorus, nitrogen, etc. The flame retardant can be used within a range that does not impair the effects of the present invention. When a flame retardant is blended, the blending amount is preferably 5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the total of the styrene monomer component and the crosslinking agent component constituting the crosslinked polymer. From the viewpoint of easily imparting excellent flame retardancy even with a small amount of addition, it is preferable to use a brominated bisphenol flame retardant as the flame retardant, and it is more preferable to use a brominated bisphenol flame retardant having a 2,3-dibromo-2-methylpropyl group and / or a brominated bisphenol flame retardant having a 2,3-dibromopropyl group, and it is even more preferable to use 2,2-bis[4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl]propane.
[0075] In addition, a flame retardant auxiliary can be appropriately blended into the HIPE foam (X) for the purpose of further improving the flame retardancy. For example, when a halogen-based flame retardant is used, if a radical generator such as dicumyl peroxide is used as the flame retardant auxiliary, the decomposition of the radical generator promotes the detachment of halogen from the flame retardant, and the flame retardancy can be improved. When a halogen-based flame retardant is used, if an antimony compound such as antimony trioxide is used as the flame retardant auxiliary, the radical trapping effect of the halogen-based flame retardant and the air blocking effect of antimony oxide act synergistically, and the flame retardancy can be improved. The flame retardant may be used alone, or two or more flame retardants with different flame retardant mechanisms may be used in combination.
[0076] The polymerization initiator is used to initiate the polymerization of the styrene monomer. As the polymerization initiator, a radical polymerization initiator can be used. More specifically, the polymerization initiator includes dilauroyl peroxide (LPO), bis(4-t-butylcyclohexyl) peroxydicarbonate (LTCP), 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(3,5,5-trimethylhexanoyl) peroxide, t-butyl peroxy piperate, t-hexyl peroxy piperate, t-butyl peroxy neoheptanoate, t-butyl peroxy neodecanoate, t-hexyl peroxy ne, and the like. Examples of the organic peroxides that can be used include decanoate, di(2-ethylhexyl)peroxydicarbonate, 1,1,3,3-tetramethylbutylperoxyneodecanoate, and benzoyl peroxide; and azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(4-dimethylvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), and 2,2'-azobis(2-methylbutyronitrile).
[0077] From the viewpoint of suppressing boiling of water during polymerization, the one-hour half-life temperature of the polymerization initiator is preferably 95° C. or lower, and more preferably 90° C. or lower. From the viewpoint of safety, in order to suppress decomposition of the polymerization initiator at room temperature, the one-hour half-life temperature of the polymerization initiator is preferably 50° C. or higher, and more preferably 55° C. or higher.
[0078] As the polymerization initiator, one or more kinds of substances can be used. From the viewpoint of shortening the polymerization time without lowering the uniformity of the apparent density of the HIPE foam (X), it is preferable to use a combination of an organic peroxide having a one-hour half-life temperature of 50°C or more and less than 70°C and an organic peroxide having a one-hour half-life temperature of 70°C or more and 90°C or less.
[0079] The polymerization initiator may be added to the organic phase or the aqueous phase. The polymerization initiator may be added to both the organic phase and the aqueous phase. When the polymerization initiator is added to the aqueous phase, a water-soluble polymerization initiator such as 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, potassium persulfate, or ammonium persulfate may be used. The amount of the polymerization initiator to be added may be, for example, within the range of 0.1 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the total of the styrene monomer and the crosslinking agent.
[0080] The emulsifier is used for forming and stabilizing a high internal phase emulsion. For example, a surfactant can be used as the emulsifier. More specifically, the emulsifier may be glycerol esters such as polyglycerol condensed ricinoleate, polyglycerol stearate, polyglycerol oleate, polyglycerol laurate, polyglycerol myristate, etc.; sorbitol esters such as sorbitan oleate, sorbitan stearate, sorbitan laurate, sorbitan laurate, sorbitan palmitate, etc.; ethylene glycol sorbitan esters; ethylene glycol esters; copolymers of polyethylene glycol and polypropylene glycol, etc. These emulsifiers may be used alone, or two or more emulsifiers may be used in combination. The amount of the emulsifier to be added may be, for example, within the range of 1 part by mass to 30 parts by mass relative to 100 parts by mass of the total of the styrene monomer, the crosslinking agent, and the emulsifier.
[0081] The electrolyte is used to impart ionic strength to the aqueous phase and to enhance the stability of the emulsion. As the electrolyte, a water-soluble electrolyte can be used. More specifically, calcium chloride, sodium chloride, magnesium chloride, sodium acetate, sodium citrate, sodium sulfate, calcium sulfate, magnesium sulfate, sodium dihydrogen phosphate, disodium hydrogen phosphate, etc. can be used as the electrolyte. The amount of the electrolyte added may be, for example, within the range of 0.01 parts by mass to 10 parts by mass relative to 100 parts by mass of the aqueous liquid.
[0082] ·Polymerization process In the polymerization step, the water-in-oil type high internal phase emulsion is filled into a reaction vessel, and then a styrene-based monomer is polymerized in the reaction vessel. In the polymerization step, for example, the high internal phase emulsion in the reaction vessel is heated to polymerize the styrene-based monomer to obtain a polymerization product (specifically, a crosslinked polymer containing water). As a method for heating the high internal phase emulsion in the polymerization step, heating with a heat transfer medium liquid such as hot water, heating with electromagnetic waves such as high frequency waves and microwaves, etc. can be suitably adopted.
[0083] The polymerization temperature in the polymerization step is adjusted depending on, for example, the type of styrene-based monomer, the type of polymerization initiator, the type of crosslinking agent, and the like.
[0084] ·Drying process By removing water from the polymerization product obtained as described above, that is, the cross-linked polymer containing water, HIPE foam (X) can be obtained (drying step). In the drying step, the polymerization product is dried using an oven, a vacuum dryer, a high-frequency / microwave dryer, or the like. Upon completion of the drying, the areas where the aqueous phase existed in the emulsion before polymerization become air bubbles in the cross-linked polymer after drying, and HIPE foam (X) can be obtained. As an example, HIPE foam (X) can be obtained by thoroughly drying the polymerization product in an oven set at 90°C until it reaches a constant weight.
[0085] ·Dehydration process In the above-mentioned production method, a dehydration step for removing a part of the water contained in the polymerized product from the polymerized product may be carried out before the drying step, if necessary. By carrying out the dehydration step before the drying step, the time required for the drying step can be further shortened. Examples of a method for removing a part of the water from the polymerized product in the dehydration step include a method of squeezing the polymerized product using a press or a method of centrifuging the polymerized product.
[0086] The dehydration of the polymerization product may be carried out at room temperature (e.g., 23° C.), but it can also be carried out at a temperature equal to or higher than the glass transition temperature of the polymerization product, for example. In this case, dehydration by squeezing or centrifugation becomes easier, and the drying time can be shortened.
[0087] In the dehydration step, it is preferable to maintain the temperature of the polymerization product at or above the glass transition temperature during the period from the start to the completion of the removal of moisture. In this way, by maintaining the temperature of the polymerization product at or above the glass transition temperature during the application of an external force in the dehydration step, the dimensions of the polymerization product are likely to be restored to approximately the dimensions before the dehydration step when the dehydration step is completed and the external force is released. As a result, the structure of the polymerization product before the dehydration step is more likely to be reflected in the HIPE foam (X) after the drying step. Furthermore, in this case, the time required for the drying step can be further shortened.
[0088] [Compression of HIPE foam (X)] The HIPE foam (X) obtained as described above is compressed to a compression ratio C represented by the following formula (1) in the range of 0.2 to 0.7 while the temperature of the HIPE foam (X) is at or above the glass transition temperature. C = (t0-t1) / t0 (1)
[0089] In the above formula (1), t0 is the thickness (unit: mm) of the HIPE foam (X) before compression, and t1 is the thickness (unit: mm) of the HIPE foam (X) in a compressed state.
[0090] Thereafter, the HIPE foam (X) is cooled to a temperature below the glass transition temperature while maintaining the compressed state, thereby stabilizing the shape of the HIPE foam (X) in the compressed state. In this manner, the apparent density of the HIPE foam (X) can be increased to within a desired range, and the HIPE foam can be obtained.
[0091] The temperature of the HIPE foam (X) during compression refers to the temperature of the center of the HIPE foam (X), that is, the center of the HIPE foam in all directions, including the length, width, and thickness. When compressing the HIPE foam (X) in the above-mentioned manner, the HIPE foam (X) may be heated and compressed simultaneously, or may be heated and then compressed while the temperature of the HIPE foam (X) is at or above the glass transition temperature. When heating and compressing are performed simultaneously, a device capable of simultaneously performing heating and compression, such as a heat press device, may be used. When heating and compressing are performed separately, a method of heating the HIPE foam (X) using an oven or the like and then compressing it using a press device may be used.
[0092] If the temperature at which the HIPE foam (X) is compressed is lower than the glass transition temperature, the HIPE foam (X) will not be softened sufficiently, and it may be difficult to compress the HIPE foam (X) while maintaining the cell wall structure or to increase the apparent density of the compressed HIPE foam.
[0093] If the compression ratio C of the HIPE foam (X) is too small, the bubbles and bubble walls of the HIPE foam are easily crushed excessively. In this case, it may be difficult to form a sufficiently large vacuum space inside the vacuum insulation material, or the bubble walls may have a structure that is not suitable for insulation, which may result in a decrease in insulation properties. Also, if the compression ratio C of the HIPE foam (X) is too large, it may be difficult to sufficiently increase the apparent density of the HIPE foam, which may result in a decrease in insulation properties.
[0094] (Vacuum insulation material) After the HIPE foam is enclosed in an outer packaging material, the gas in the internal space surrounded by the outer packaging material is exhausted to obtain a vacuum insulation material. As shown in Fig. 4, the vacuum insulation material 2 has an outer packaging material 21 and a core material 22 enclosed in the outer packaging material 21. The pressure in the internal space surrounded by the outer packaging material 21 in the vacuum insulation material 2 is lower than atmospheric pressure. From the viewpoint of obtaining better insulation properties, the degree of vacuum inside the vacuum insulation material is preferably 10 Pa or less, and more preferably 5 Pa or less.
[0095] [Core material] The core material 22 of the vacuum insulation material 2 is composed of HIPE foam 1 having an apparent density and a ratio of compressive stress at 5% strain to compressive stress at 50% strain within the above-mentioned specific range. Since the specific configuration of the HIPE foam 1 used as the core material 22 is as described above, the above-mentioned explanation of the HIPE foam can be referred to as appropriate for the specific configuration of the HIPE foam 1.
[0096] [Outer packaging material] The packaging material of the vacuum insulation material has low water vapor permeability and gas permeability, i.e., gas barrier properties. This makes it possible to maintain the pressure in the internal space of the vacuum insulation material lower than atmospheric pressure and maintain the heat insulating properties of the vacuum insulation material. As the packaging material, for example, a multilayer film having a gas barrier layer made of a material having gas barrier properties and a heat-sealed layer laminated on one side of the gas barrier layer is used.
[0097] The gas barrier layer may be made of a metal foil or a metal-deposited thin film made of a metal such as aluminum. The thermal adhesion layer may be made of a polyolefin resin film such as polyethylene or polypropylene, a polyester resin film such as polyethylene terephthalate or polybutylene terephthalate, or a polyvinyl chloride resin film such as polyvinylidene chloride.
[0098] The outer packaging material preferably further has a protective film layer laminated on the back side of the surface of the gas barrier layer having the heat-sealing layer. Examples of materials constituting the protective film layer include polyamide resin films such as nylon; polyester resin films such as polyethylene terephthalate and polybutylene terephthalate. The number of the protective film layers may be one or more. For example, the outer packaging material may have one protective film layer on the back side of the surface of the gas barrier layer having the heat-sealing layer laminated thereon, or may have two or more protective film layers laminated together. The thickness of the outer packaging material is preferably 30 μm or more and 300 μm or less.
[0099] [Thermal conductivity of vacuum insulation material] The thermal conductivity of the vacuum insulation material is preferably less than 6.0 mW / (m·K). In this case, the thermal insulation property of the vacuum insulation material can be further improved. From the viewpoint of improving the thermal insulation property of the vacuum insulation material, the lower limit of the thermal conductivity of the vacuum insulation material is not particularly limited, but when the specific HIPE foam is used as the core material, the lower limit of the thermal conductivity of the vacuum insulation material is about 3.0 mW / (m·K).
[0100] The thermal conductivity of the vacuum insulation material can be measured by the heat flow meter method specified in JIS A1412-2:1999. More specifically, the thermal conductivity of the HIPE foam can be measured using, for example, a thermal conductivity measuring device ("HC-074 / 200" manufactured by Eiko Seiki Co., Ltd.). In measuring the thermal conductivity, first, a flat core material with a length of 180 mm, a width of 180 mm, and a thickness of 10 mm is prepared from the HIPE foam. This core material is enclosed in an outer packaging material to prepare a vacuum insulation material with an outer dimension including the heat-sealed part of the outer packaging material of a length of about 200 mm, a width of about 200 mm, and a thickness of 10 mm. The vacuum insulation material thus obtained is used as a test specimen, and one surface in the thickness direction of the test specimen is brought into contact with a high-temperature surface, and the other surface is brought into contact with a low-temperature surface, and a temperature difference is applied between the high-temperature surface and the low-temperature surface. Then, the heat flow passing through the test specimen in a steady state is measured, and the thermal conductivity can be calculated based on the obtained heat flow, etc. In addition, when measuring thermal conductivity, the temperature of the hot surface should be 33°C, the temperature of the cold surface should be 13°C, and the average temperature of the test specimen should be 23°C.
[0101] (Manufacturing method of vacuum insulation material) The method for producing the vacuum insulation material is not particularly limited, and any known method can be used. For example, the surface of the core material is wrapped with an outer packaging material, and then the gas present in the internal space of the vacuum insulation material is exhausted to make the internal space a vacuum state, and the core material is sealed with the outer packaging material while maintaining this vacuum state, thereby obtaining the vacuum insulation material.
[0102] A core material made of at least HIPE foam is enclosed in the internal space of the vacuum insulation material surrounded by the outer packaging material. In addition to the core material, an adsorbent that adsorbs moisture and / or gas may be enclosed in the internal space of the vacuum insulation material. In this case, the pressure in the internal space of the vacuum insulation material can be kept lower than atmospheric pressure for a longer period of time. As a result, the insulating properties of the vacuum insulation material can be maintained for a longer period of time. EXAMPLES
[0103] The HIPE foam, its manufacturing method, and the vacuum insulation material are described below. The styrene monomer, crosslinking agent, emulsifier, and polymerization initiator used in the examples and comparative examples, and their abbreviations are as follows:
[0104] Styrene monomers St: styrene Crosslinking agent DVB: Divinylbenzene (molecular weight 130, "DVB-570" manufactured by Nippon Steel Chemical & Material Co., Ltd., purity 57%)
[0105] Polymerization initiator LPO: Dilauryl peroxide (NOF Corporation "Perloyl (registered trademark) L", 1-hour half-life temperature: 79.5°C) LTCP: Bis(4-t-butylcyclohexyl) peroxydicarbonate (NOF Corporation, "Peroyl TCP", 1-hour half-life temperature: 57.5°C)
[0106] Example 1 In this example, first, a HIPE foam (X) was produced by the following method.
[0107] [Preparation of HIPE foam (X)] Into a 3 L glass vessel equipped with a stirrer with a torque converter, 82.5 parts by mass of styrene as a styrene monomer, 10 parts by mass of divinylbenzene as a crosslinking agent, 7.5 parts by mass of polyglycerin condensed ricinoleate as an emulsifier, 0.5 parts by mass of dilauroyl peroxide and 0.5 parts by mass of bis(4-t-butylcyclohexyl)peroxydicarbonate as polymerization initiators were charged. These were mixed in the glass vessel to form an organic phase.
[0108] Next, 0.10 parts by mass of calcium chloride was dissolved as an electrolyte in 1900 parts by mass of deionized water to prepare an aqueous phase. Then, while stirring the organic phase at a rotation speed of 400 rpm, the aqueous phase at a temperature of 20°C was added to the glass container at a rate of about 450 g / min. Stirring was continued for 10 minutes after the addition of the deionized water was completed to prepare a water-in-oil (i.e., W / O) type high internal phase emulsion. The stirring power density after emulsification was completed was 1.4 kW / m 3 The stirring power density (unit: kW / m 3 ) is calculated by calculating the power (unit: kW) from the torque (unit: N m) and rotation speed (unit: rpm) of the agitator, and the volume of the contents (unit: m 3 ) can be calculated by dividing it by
[0109] Next, the stirring power density was set to 0.1 kW / m 3 The pressure in the glass container was then lowered to 20°C, and an aspirator was connected to the glass container to reduce the pressure inside the container, thereby removing the microbubbles contained in the emulsion. Ten minutes after the start of the reduction in pressure, the stirring was stopped and the pressure inside the container was returned to atmospheric pressure. The temperature inside the glass container was maintained at 20°C using a chiller from the start to the end of the stirring.
[0110] The high internal phase emulsion thus obtained was filled into a vessel having a length of 200 mm, a width of 200 mm, and a depth of 40 mm. The organic phase of the high internal phase emulsion in the reaction vessel was polymerized in a thermostatic water bath at 70° C. for about 10 hours to form a polymerization product (i.e., a crosslinked polymer containing water) in the reaction vessel. After the polymerization was completed, the reaction vessel was removed from the thermostatic water bath and cooled to room temperature.
[0111] Next, the polymerization product taken out of the reaction vessel was washed with water. After the washing, the polymerization product was dehydrated and then dried in an oven at 90°C until it reached a constant weight, thereby obtaining a HIPE foam (X). The outer dimensions of the HIPE foam (X) obtained after drying were about 200 mm long, about 200 mm wide, and about 40 mm thick. Next, the HIPE foam (X) was cut into a plate shape with a length of about 180 mm, a width of about 180 mm, and a thickness of about 25 mm using a band saw, and both sides were polished using a drum sander to a thickness of 20 mm. The HIPE foam (X) thus formed was heated at a temperature of 200°C for 30 minutes and cured. The thickness t0 of the HIPE foam (X) after curing was 20 mm.
[0112] The composition of each component in the HIPE foam (X) of this example is shown in Table 1. The content of each component (styrene monomer and crosslinking agent) in the HIPE foam (X) can be calculated from the blending amount of each component (for the crosslinking agent, the blending amount excluding impurities) at the time of blending and the total blending amount of the styrene monomer component and the crosslinking agent component (excluding impurities).
[0113] [Preparation of core material] Next, the HIPE foam (X) was compressed while being heated to a temperature equal to or higher than the glass transition temperature, and cooled to a temperature lower than the glass transition temperature while maintaining the compressed state, to produce a core material. Specifically, the HIPE foam (X) obtained by the above method was supplied to a heat press device with a hot plate temperature of 200°C, and heated for 5 minutes to make the temperature of the HIPE foam (X) 150°C or higher, thereby softening it. After softening, the HIPE foam (X) was compressed so that the thickness t1 after compression was 10 mm. Then, the HIPE foam was cooled while maintaining this thickness, and the shape of the HIPE foam was stabilized. As a result, a HIPE foam that serves as the core material of the vacuum insulation material was obtained. The compression ratio C of the HIPE foam (X) in this example was as shown in Table 2.
[0114] [Preparation of vacuum insulation material] Next, the core material was placed in the outer packaging material, and the inner space of the outer packaging material was decompressed, and then the core material was enclosed in the outer packaging material to produce a vacuum insulation material. As the outer packaging material, a multilayer film was used, which had a gas barrier layer made of aluminum foil, a heat-sealed layer made of polyethylene and laminated on one side of the gas barrier layer, and a protective film layer made of a laminate of a nylon film and a polyethylene terephthalate film and laminated on the back side of the heat-sealed layer in the gas barrier layer. First, two square multilayer films with a length of 230 mm and a width of 230 mm were prepared. Next, the two multilayer films were overlapped so that the heat-sealed layer was on the inside, and three sides of the multilayer film were heat-sealed to obtain a bag-shaped outer packaging material with one side open.
[0115] After placing a core material made of compressed HIPE foam into this outer packaging material, the gas present in the inner space of the outer packaging material was exhausted using a vacuum packaging machine (MDJ Co., Ltd. "MDKT500-RD"). Then, after continuing the exhaust for another 60 seconds from the point when the pressure in the inner space reached 1 Pa, the open side of the outer packaging material was heat-sealed to seal the core material in the outer packaging material. Then, the end not including the core material was cut to a length of 200 mm, a width of 200 mm, and a thickness of 40 mm. As a result, the vacuum insulation material of Example 1 was obtained.
[0116] (Examples 2 to 4) In these examples, the HIPE foam and the vacuum insulation material were produced in the same manner as in Example 1, except that the thickness t0 and the compression rate C of the HIPE foam (X) were changed as shown in Table 2. The thickness t1 of the HIPE foam in the compressed state in Examples 2 to 4 was the same as the thickness t1 of the HIPE foam in Example 1.
[0117] (Examples 5 to 6) In these examples, HIPE foams and vacuum insulation materials were obtained in the same manner as in Example 1, except that the blending amount of the water phase and the stirring power density were changed as shown in Table 1.
[0118] (Examples 7 to 8) In these examples, the HIPE foam and the vacuum insulation material were obtained in the same manner as in Example 1, except that the thickness t0 of the HIPE foam (X) and the thickness t1 of the HIPE foam in a compressed state were changed as shown in Table 2. The compression ratios C before and after compression in Examples 7 to 8 were the same as the compression ratio C in Example 1.
[0119] (Examples 9 to 10) In these examples, the HIPE foam and the vacuum insulation material were produced in the same manner as in Example 1, except that the stirring power density was changed as shown in Table 1.
[0120] Comparative Example 1 The HIPE foam of Comparative Example 1 is a HIPE foam (X) that is not compressed after the polymerization product is removed from the reaction vessel and subjected to the dehydration and drying processes. The manufacturing method of the HIPE foam of Comparative Example 1 is the same as the manufacturing method of the HIPE foam in Example 1, except that the thickness t0 of the HIPE foam (X) is changed as shown in Table 4, and compression is not performed after the dehydration and drying processes.
[0121] Comparative Example 2 In Comparative Example 2, a HIPE foam and a vacuum insulation material were produced in the same manner as in Example 1, except that the thickness t0 and compression rate C of the HIPE foam (X) were changed as shown in Table 4.
[0122] (Comparative Examples 3 to 4) In these comparative examples, the HIPE foam and vacuum insulation material were obtained in the same manner as in Example 1, except that the blend ratios of the oil phase and the water phase, the stirring power density, and the thickness t0 of the HIPE foam (X) were changed. The blend ratios of the oil phase, the water phase, and the stirring power density in these comparative examples are as shown in Table 3. The thickness t0 of the HIPE foam (X) in these comparative examples is as shown in Table 4.
[0123] Next, the evaluation methods for each of the physical properties shown in Tables 1 to 4 will be described.
[0124] [Apparent density of HIPE foam (X)] The mass (unit: kg) of the HIPE foam (X) before compression is expressed as the volume (unit: m 3 ) to obtain the apparent density (unit: kg / m 3 ) was calculated.
[0125] [Glass transition temperature Tg of HIPE foam (X)] The glass transition temperature Tg of the HIPE foam (X) before compression was measured based on JIS K7121:1987. Specifically, first, the HIPE foam (X) was cut to obtain a test piece. Next, the test piece was conditioned based on "(3) Measurement of glass transition temperature after a certain heat treatment" in "3. Conditioning of test piece" in JIS K 7121:1987. Then, the conditioned test piece was subjected to differential scanning calorimetry (DSC) to obtain a DSC curve. The midpoint glass transition temperature in the DSC curve obtained in this way was taken as the glass transition temperature Tg of the HIPE foam (X).
[0126] [Average bubble diameter of HIPE foam (X)] Using a feather blade, samples for observation were cut out from the center of the lateral direction and thickness direction of the HIPE foam (X) before compression, and from the center of the thickness direction at both ends of the lateral direction. Next, each sample was observed using a low-vacuum scanning electron microscope ("Miniscope (registered trademark) TM3030Plus" manufactured by Hitachi High-Tech Science Corporation), and enlarged photographs of the cross sections of the samples were taken.
[0127] - Sample pretreatment: The sample was treated to make it conductive using a metal coating device ("MSP-1S" manufactured by Vacuum Device Co., Ltd.) Au-Pd was used as the target electrode. Magnification: 50x Acceleration voltage: 5kV Observation conditions: Surface (low magnification) Observation mode: Secondary electrons (standard)
[0128] Next, the enlarged photograph was analyzed using image processing software (NanoHunter NS2K-Pro, manufactured by NanoSystems Co., Ltd.), and the bubble diameter (circle equivalent diameter) of each bubble present on the enlarged photograph was calculated. The arithmetic mean of these bubble diameters was then taken as the average bubble diameter of the HIPE foam (X). The detailed analysis procedure and conditions were as follows.
[0129] (1) Monochrome conversion (2) Smoothing filter (3x3, 8 neighborhoods, number of processes = 1) (3) Density unevenness correction (brighter than background, size = 5) (4) NS binarization (darker than background, clarity = 9, sensitivity = 1, noise removal, density range = 0 to 255) (5) Contraction (8 neighbors, number of processes = 1) (6) Image selection based on feature (area) (50~∞μm 2 (Only select 8 neighbors) (7) Dilation without connections to neighbors (8 neighbors, number of processes = 3) (8) Measurement of circle equivalent diameter (calculated from area, 8th neighborhood)
[0130] [Average strut width of HIPE foam (X)] First, the HIPE foam (X) before compression was cut at an arbitrary cross section to expose the cut surface. Next, the cut surface was observed using a scanning electron microscope or the like, and an enlarged photograph of the cut surface was obtained. On this enlarged photograph, 20 struts were randomly selected, and the width of the narrowest part of each strut was measured. The arithmetic mean value of the strut widths obtained in this way was taken as the average strut width.
[0131] [HIPE Foam (X) Compression Properties] A test piece of 50 mm in length, 50 mm in width, and 20 mm in thickness was cut out from near the center of the HIPE foam (X) before compression, excluding the skin surface, i.e., the surface that was in contact with the container during polymerization. The test piece was left to stand in an environment of 23°C temperature and 50% humidity to condition the test piece. Then, using the condition-conditioned test piece, the compressive stress at 5% strain σx5 and the compressive stress at 50% strain σx of the HIPE foam (X) were measured based on JIS6767:1999. 50 Based on these values, the compressive stress σx of HIPE foam (X) at 50% strain was calculated. 50 Ratio of compressive stress at 5% strain σx5 to σx5 / σx 50 was calculated.
[0132] The compression test was performed using a bench-top precision universal testing machine (Shimadzu Corporation, "AGS-10kNX") at a compression speed of 10 mm / min.
[0133] [Molecular weight Mc between crosslinks of HIPE foam (X)] Dynamic viscoelasticity measurements were performed on the HIPE foam (X) before compression under the following measurement conditions: frequency: 1 Hz, load: 98 mN, deformation mode: compression, and a T-E' curve was obtained. In the obtained T-E' curve, any temperature T (unit: K) within the range of Tg+50°C to Tg+80°C, the storage modulus E' (unit: kPa) at that temperature T, and the apparent density ρ (unit: kg / m 3 ) and the molecular weight Mc between crosslinking points of the HIPE foam (X) was calculated based on the following formula (1). Mc = 2(1 + μ)ρRT / E' (I)
[0134] In the above formula (I), μ is the Poisson's ratio and R is the gas constant. The value of the Poisson's ratio μ is specifically set to 0.5, and the value of the gas constant R is specifically set to 8.314 J / (K mol).
[0135] [Apparent density of HIPE foam] The mass (unit: kg) of the HIPE foam after compression and cooling was calculated from the external dimensions and the volume (unit: m 3 ) to obtain the apparent density of the compressed HIPE foam (unit: kg / m 3 ) was calculated.
[0136] [HIPE foam compression properties] The method for measuring the compression properties of the HIPE foam was the same as that for the HIPE foam (X), except that the HIPE foam after compression and cooling was used instead of the HIPE foam (X) before compression.
[0137] [Manufacturability] When exhausting the gas present in the internal space during the manufacturing process of vacuum insulation material, the time required from the start of exhaust until the pressure reached 1 Pa, and the pressure reached when sealing the outer packaging material were measured and are shown in Tables 2 and 4.
[0138] [Thermal insulation] The thermal insulation properties of the vacuum insulation material were evaluated based on the thermal conductivity of the vacuum insulation material. The thermal conductivity was measured by the heat flow meter method specified in JIS A1412-2:1999 using the vacuum insulation material as a test specimen. More specifically, the test specimen was attached to a thermal conductivity measuring device ("HC-074 / 200" manufactured by Eiko Seiki Co., Ltd.) so that one surface in the thickness direction of the test specimen was in contact with the high temperature surface of the device and the other surface was in contact with the low temperature surface. Thereafter, the temperature of the high temperature surface was set to 33°C, and the temperature of the low temperature surface was set to 13°C. Then, the thermal conductivity was measured after the temperature distribution of the test specimen reached a steady state. The average temperature of the test specimen during the thermal conductivity measurement was 23°C.
[0139] In the "Evaluation" column for "Insulation" in Tables 2 and 4, if the thermal conductivity of the vacuum insulation material is less than 6.0 mW / (m K), it is recorded as "Good," and if it is 6.0 mW / (m K) or more, it is recorded as "Poor."
[0140] [Shape retention] The shape retention of the vacuum insulation material was evaluated based on the shrinkage rate of the core material due to reduced pressure. Specifically, the thickness of the thinnest part of the vacuum insulation material was measured, and the thickness of the outer packaging material was subtracted from the measured thickness to calculate the thickness of the core material in the vacuum insulation material. Next, the amount of shrinkage of the core material due to reduced pressure was calculated by subtracting the thickness of the core material in the vacuum insulation material from the thickness of the core material before being enclosed in the outer packaging material. The shrinkage rate of the core material (unit: %) was determined as the ratio of the amount of shrinkage of the core material to the thickness of the core material before being enclosed in the outer packaging material, expressed as a percentage. In the "Evaluation" column of "Shape Retention" in Tables 2 and 4, "Good" was written when the shrinkage rate of the core material was 10% or less, and "Poor" was written when it exceeded 10%.
[0141] [Table 1]
[0142] [Table 2]
[0143] [Table 3]
[0144] [Table 4]
[0145] As shown in Table 2, the apparent density and compressive stress at 50% strain σ of the HIPE foams of Examples 1 to 10 are 50 Ratio of compressive stress σ5 at 5% strain to σ5 / σ 50 Therefore, the vacuum insulation materials using the HIPE foams of Examples 1 to 10 as the core material have excellent manufacturability, are lightweight, and have good thermal insulation properties.
[0146] On the other hand, as shown in Table 4, the vacuum insulation material using the HIPE foam of Comparative Example 1 as the core material has poor insulation properties. This is thought to be because the HIPE foam of Comparative Example 1 is not compressed in a state heated to a temperature equal to or higher than the glass transition temperature during the manufacturing process.
[0147] The HIPE foam of Comparative Example 2 was compressed excessively during the manufacturing process, so the compression ratio C was small, and the compressive stress σ 50 Ratio of compressive stress σ5 at 5% strain to σ5 / σ 50 Therefore, the vacuum insulation material using the HIPE foam of Comparative Example 2 as the core material has poor heat insulation properties.
[0148] The apparent density of the HIPE foam of Comparative Example 3 is lower than the specific range. Therefore, in the vacuum insulation material using the HIPE foam of Comparative Example 3 as a core material, when the internal space is decompressed, the core material cannot withstand the pressure difference between the inside and outside of the vacuum insulation material, and shrinks significantly.
[0149] The HIPE foam of Comparative Example 4 has an apparent density higher than the specific range because the HIPE foam (X) having a relatively high apparent density is compressed. Therefore, the vacuum insulation material using the HIPE foam of Comparative Example 4 as a core material has poor thermal insulation properties.
[0150] The above describes specific embodiments of the vacuum insulation material and HIPE foam of the present invention based on the examples, but the embodiments of the vacuum insulation material and HIPE foam of the present invention are not limited to the embodiments, and the configuration can be changed as appropriate within the scope that does not depart from the spirit of the present invention. [Explanation of symbols]
[0151] 1 HIPE Form
Claims
1. A plate-shaped HIPE foam used as a core material in a vacuum insulation material having an outer packaging material and a core material enclosed in the outer packaging material, The apparent density of the HIPE foam is 65 kg / m 3 More than 140kg / m 3 is as follows: Compressive stress σ of the HIPE foam at 50% strain 50 Compressive stress at 5% strain σ 5 Ratio of σ 5 / σ 50 is greater than or equal to 0.17 and less than or equal to 0.
50.
2. Compressive stress σ of the HIPE foam at 5% strain 5 The HIPE foam of claim 1 , wherein the elastic modulus is 105 kPa or more.
3. 2. The HIPE foam of claim 1, wherein said HIPE foam is comprised of a crosslinked polymer of a styrene-based monomer.
4. The present invention has an outer packaging material and a core material enclosed within the outer packaging material, A vacuum insulation material, wherein the core material is composed of the HIPE foam according to any one of claims 1 to 3.
5. Apparent density 35kg / m 3 More than 70kg / m 3 Prepare a plate-shaped HIPE foam (X) as shown below. The HIPE foam (X) is compressed to a compression ratio C of 0.2 or more and 0.7 or less, the compression ratio C being represented by the following formula (1) being in a state where the temperature of the HIPE foam (X) is equal to or more than the glass transition temperature of the HIPE foam (X); The HIPE foam (X) in the compressed state is cooled to a temperature lower than the glass transition temperature, whereby the compressive stress at 50% strain σ 50 Compressive stress at 5% strain σ 5 Ratio of σ 5 / σ 50 A method for producing a HIPE foam, comprising forming a HIPE foam having a .lambda. of 0.17 or greater and 0.50 or less. C=(t 0 -t 1 ) / t 0 ・・・(1) (However, t in the above formula (1) 0 is the thickness (unit: mm) of the HIPE foam (X) before compression, and t 1 is the thickness (unit: mm) of the HIPE foam (X) in the compressed state.
6. The method for producing a HIPE foam according to claim 5, wherein the average strut width of the HIPE foam (X) before compression is 2 μm or more and 10 μm or less.
7. The compressive stress σx at 5% strain of the HIPE foam (X) before compression 5 The method for producing a HIPE foam according to claim 5, wherein the compressive strength is 140 kPa or more.
Citation Information
Patent Citations
Extruded open-cell microcellular foam and method of making same
JP1999504362A